Diseño audiovisual enfocado a facilitar la difusión de jóvenes emprendedores del catón Mejía. - Iza Caguana, Cristian José (2018)
This research pretends to emphazise young entrepreneurs´talent with a great spirit in order to become capable of changing different productive environments.The lack of advertising spaces of free access in the different dissemination plattforms demanded the necessity of developing an audiovisual proposal This search seeks to develop an audiovisula production with a high, quality, technique and creativity, it is supported with interactive visual elements of gaphics to promote the young entrepreneurs´talent in Mejía canton. The methodology of this research was focused on the critical and communicative paradigm, qualitative and quantitative approach, dialectics method. All of them allowed to carry out a systematic and delimited process for the information collection about categories which got involved in the proposal development and the methodological design was life stories about interviewed young people.The techniques applied were survey and interview, their instruments were questionnaire and interview guide to get a audiovisual narrative of the documentary. The development of this audiovisual proposal is fundamental because to recognize the young entrepreneurs´talent by means of the usage of digital and free plattforms, where they provide the oportunity to express their services to the society.This investigation contributes with the creation of dissemination products through the facts films with technical elements, scripts and storyboards, that helped to the flow of tis work. In the technological field, there were some equipments like SLR cameras of high resolution, tripods, microphones and lights, all of them provide dynamism and they show the facts and real experiences that reflect true information so that they can be subjected to the analysis of the objective public, as direct consummers of the products or services offered.